CHALLENGE BOARD SEBAGAI MEDIA UNTUK MENURUNKAN PERILAKU BUANG AIR BESAR DI CELANA (SOILING) PADA ANAK - Ulin Nuri Mauludiyah (Universitas Negeri Makassar, 2020)
The study aims to lower bowel behavior in the pants (soiling) of children. The subject is 9 year old boy. Researchers intervene using the challenge board as a medium to lower the behavior. The Challenge board is a medium that is developed by the rules of the response cost technique. This therapy is preceded by providing explanation to the subject about how to defecate well and correctly. Then proceed by making a deal that the behavior of defecation in the pants (soiling) must be changed, before enters in the stage of completing the given challenges. The method used in research is qualitative with a case study approach. The results of this study show that the use of the Challenge Board is effective to lower bowel behavior in the pants (soiling) on the subject.